Progression of subcortical atrophy in mild Parkinson's disease and its impact on cognition. (10th December 2016) - Foo, H.; Mak, E.; Yong, T. T.; Wen, M. C.; Chander, R. J.; Au, W. L.; Sitoh, Y. Y.; Tan, L. C. S.; Kandiah, N.
Abstract : Background and purpose: Mild cognitive impairment (MCI) is associated with pronounced grey matter atrophy in various brain regions. However, the association between atrophy patterns and progression from no cognitive impairment (NCI) to Parkinson's disease (PD)‐MCI is not clearly known. We investigated the pattern and progression of atrophy in subcortical structures and its impact on cognition in patients with mild PD. Methods: Sixty‐five patients with mild PD with baseline and longitudinal clinical and neuropsychological assessments, and structural magnetic resonance imaging scans were studied. Movement Disorder Society Task Force criteria were used to classify patients with PD into PD‐NCI ( n = 54) and PD‐MCI ( n = 11). Based on progression over time, those who remained without cognitive impairment were classified as PD‐stable ( n = 42) and those who converted to MCI over 18 months were classified as PD‐converters ( n = 12). FreeSurfer was used to measure cortical thickness and subcortical volumes at baseline and follow‐up. Results: Parkinson's disease‐MCI showed baseline thalamus atrophy and progressive atrophy in the thalamus, caudate, presubiculum, cornu ammonis 1 and 2–3, and significant memory and executive dysfunction compared with PD‐NCI. PD‐converters had greater accumbens atrophy at baseline and progressive atrophy in the thalamus, caudate and accumbens with dysfunctions in memory and executive domains. Conclusions: Progression of cognitive impairment in non‐demented PD is associated with a specific pattern of subcortical atrophy. Findings from this study will allow future studies to investigate in the role of subcortical structures as a biomarker for PD dementia.